Late-onset Hereditary ATTR Amyloidosis with a Novel p.P63S (P43S) Transthyretin Variant - Aono, Yuya (Intern Med, 2020)
The patient was an 82-year-old Japanese man with no family history suggestive of amyloidosis. He developed bilateral leg edema and shortness of breath and was referred to our hospital. An electrocardiogram showed atrial fibrillation with right bundle branch block. Echocardiography showed concentric LV hypertrophy. An endomyocardial biopsy showed severe ATTR amyloid deposits. A genetic analysis of the transthyretin (TTR) gene revealed a heterozygous c.187C＞T missense variant resulting in p.P63S (P43S). In silico analyses predicted that this variant only modestly altered the structure and function of the TTR protein. The p.P63S variant might be associated with an elderly-onset cardiac-dominant ATTRv phenotype.